Age‐related differences of γ‐aminobutyric acid (GABA)ergic transmission in human colonic smooth muscle. Issue 3 (25th August 2021) - Zizzo, Maria Grazia; Cicio, Adele; Raimondo, Stefania; Alessandro, Riccardo; Serio, Rosa
Abstract: Background: Enteric neurons undergo to functional changes during aging. We investigated the possible age‐associated differences in enteric γ‐aminobutyric acid (GABA)ergic transmission evaluating function and distribution of GABAergic receptors in human colon. Methods: Mechanical responses to GABA and GABA receptor agonists on slow phasic contractions were examined in vitro as changes in isometric tension in colonic muscle strips from young (<65 years old) and aged patients (>65 years old). GABAergic receptor expression was assessed by quantitative RT‐PCR. Key Results: In both preparations GABA induced an excitatory effect, consisting in an increase in the basal tone, antagonized by the GABAA receptor antagonist, bicuculline, and potentiated by phaclofen, GABAB receptor antagonist.Tetrodotoxin (TTX) and atropine‐sensitive contractile responses to GABA and GABAA receptor agonist, muscimol, were more pronounced in old compared to young subjects. Baclofen, GABAB receptor agonist, induced a TTX‐sensitive reduction of the amplitude of the spontaneous. Nω–nitro‐l ‐arginine methyl ester (L‐NAME), nitric oxide (NO) synthase inhibitor abolished the inhibitory responses in old preparations, but a residual responses persisted in young preparations, which in turn was abolished by suramin, purinergic receptor antagonist. α3–GABAA receptor subunit expression tends to change in an age‐dependent manner. Conclusions and inferences: Our results reveal age‐related differences in GABAergic transmission in human colon. At all the age tested GABA regulates muscular contractility modulating the activity of the intrinsic neurons. Activation of GABAA receptor, through acetylcholine release, induces contraction, which increases in amplitude with age. GABAB receptor activation leads to neural release of NO and purines, being a loss of purinergic‐component in aged group. Abstract : Age‐related differences occur in GABAergic transmission in human colon. At all the age tested GABA regulates muscular contractility. GABAA‐contractile effects, via acetylcholine release, increase in amplitude with age.GABAB‐inhibitory effects are via neural NO and purines, being a purinergic‐component loss in aged group.